(untitled) (PYC Nepal Journal of Management, 2015)
The paper aims to provide empirical evidence on impact of role conflict on work life balance and career success in the hospitals in Kathmandu valley. The structured questionnaire survey of 100 doctors and nurses was made in two hospitals - Tribhuvan University Teaching Hospital and B & B Hospital. The study followed descriptive research design and tested the reliability with Cronbach’s alpha. Correlation and regression analyses were carried on and proposed hypotheses were tested. The significant negative impact of role conflict was found on work life balance. Further, the negative effect of role conflict was also found on career success.